2011
DOI: 10.3855/jidc.1505
|View full text |Cite
|
Sign up to set email alerts
|

Nitrostative stress status during seasonal and pdmH1N1 infection in Iraq

Abstract: Introduction: Influenza A virus infection is associated with oxidative and nitrosative stress. This study aimed to assess nitrosative stress in pandemic H1N1 (pdmH1N1) and seasonal influenza A infected patients. Methodology: The study included the following subjects: 20 patients infected with seasonal (negative one-step probe RT-PCR) influenza and 12 patients infected with pdmH1N1 (positive, one-step probe RT-PCR) influenza during the 2009 pandemic in Iraq. Twenty healthy subjects served as controls. Serum nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…The present study indicates that CFS patients with antecedents of severe infection have higher biological and EMG disorders than other patients who solely reported practice of high physical activity before the occurrence of fatigue symptoms. It is well documented that acute infection constitutes a stress responsible for an oxidative stress [21][22][23][24]. Our major observation was that infection was responsible for lengthened alterations of the resting oxidant status.…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…The present study indicates that CFS patients with antecedents of severe infection have higher biological and EMG disorders than other patients who solely reported practice of high physical activity before the occurrence of fatigue symptoms. It is well documented that acute infection constitutes a stress responsible for an oxidative stress [21][22][23][24]. Our major observation was that infection was responsible for lengthened alterations of the resting oxidant status.…”
Section: Discussionmentioning
confidence: 72%
“…These authors [19] have hypothesized that the deregulation of pump activities could result from an increased fluidity of the sarcoplasmic membrane due to the ROS-induced formation of lipid hydroperoxides. It is well documented that severe bacterial [20] and viral [21][22][23][24][25] infections, including the H1N1 influenza [24,25], induce an oxidative stress. Thus, infection could be responsible for an altered membrane excitability due to reduced K + exchanges through the muscle membrane.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have reported on the relationships among increases and decreases in iNOS expression, nitrate and nitrite concentrations, and the severity of the infection or successful treatment for viral infections, as for other infectious agents [57][58][59]. Patients infected with HIV, in the AIDS stage and showing opportunistic infections, had higher nitrite concentrations in serum than those who were in the asymptomatic phase of infection [60].…”
Section: Nitric Oxide As a Prognostic Markermentioning
confidence: 99%